GAMBARAN TINGKAT STRES ORANG TUA SISWA SEKOLAH DASAR SELAMA PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 - Darmayanti, Ni Made Sri; Sawitri, Ni Komang Ari; Swedarma, Kadek Eka (Coping: Community of Publishing in Nursing, 2022)
Some parents experience obstacles during distance learning such as difficulties in motivating or improving children's mood to learn, difficulties in teaching children, quota and network constraints, and difficulties in assisting children in learning. The purpose of this study was to describe the stress level of parents of SD Negeri X students in connection with distance learning during the COVID-19 pandemic. This research is a quantitative descriptive study by distributing online questionnaires to 85 parents of SD Negeri X students using proportionate stratified random sampling technique. The measuring instrument used was a Perceived Stress Scale 10 questionnaires which has been modified by the researcher. Based on the results of the study, it was found that the median age of parents is 37 years with the youngest age being 24 years old, and the oldest age being 61 years old. The majority of the parents are female, with high school education, with working status, coming from middle income group, only use one facility in the form of a handphone, with smooth internet network condition, with subsidized quota, can use learning applications independently, and class II and IV. The majority of stress levels from parents is moderate stress.